2021
DOI: 10.1371/journal.pcbi.1008732
|View full text |Cite
|
Sign up to set email alerts
|

Positive interactions within and between populations decrease the likelihood of evolutionary rescue

Abstract: Positive interactions, including intraspecies cooperation and interspecies mutualisms, play crucial roles in shaping the structure and function of many ecosystems, ranging from plant communities to the human microbiome. While the evolutionary forces that form and maintain positive interactions have been investigated extensively, the influence of positive interactions on the ability of species to adapt to new environments is still poorly understood. Here, we use numerical simulations and theoretical analyses to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Only few studies on ER have incorporated species interactions and community dynamics and it is currently unclear which conditions influence the probability of ER. For example, studies on mutualistic interactions [16] have shown a decrease in the probability of ER while studies focusing on antagonistic interactions [14,15,17] found a decrease or increase in the probability of ER. An important determinant for ER in communities is how many species are threatened by extinction and their interactions within the community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only few studies on ER have incorporated species interactions and community dynamics and it is currently unclear which conditions influence the probability of ER. For example, studies on mutualistic interactions [16] have shown a decrease in the probability of ER while studies focusing on antagonistic interactions [14,15,17] found a decrease or increase in the probability of ER. An important determinant for ER in communities is how many species are threatened by extinction and their interactions within the community.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies have started to integrate the effect of multispecies interaction into research on ER [11][12][13][14][15][16]. There are however only few studies exploring ER in communities with multiple species [17,18] and the conditions under which populations can be rescued through evolutionary change in communities are still poorly explored [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cross-feeding), for example, might increase alpha and gamma diversities, because such interactions enable species to coexist [72]. This could result in an increase in beta diversity because the extinction of one species increases its partner species' extinction probability [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…As species interact with other species, it is, however, possible that changes in their interactions and indirect ecological and evolutionary processes affect the demography of a population [9][10][11] and thus the probability of rescue. Theoretical studies have started to integrate the effect of multi-species interaction into research on ER [12][13][14][15][16][17]. There are, however, only few studies exploring ER in communities with multiple species [18,19], and the conditions under which species can be rescued through evolutionary change in communities are still poorly explored [20].…”
Section: Introductionmentioning
confidence: 99%